Autonomous driving how the driverless revolution will change the world - Herrmann, Andreas 1964-; Brenner, Walter 1958-; Stadler, Rupert 1963- (Emerald Publishing, 2018)
The technology and engineering behind autonomous driving is advancing at pace. This book presents the latest technical advances and the economic, environmental and social impact driverless cars will have on individuals and the automotive industry